Students' Perception of The Use of The Grammarly Application in Their Writing - Andi Anugrah Surya Ardhy (ETERNAL (English, Teaching, Learning and Research Journal), 2023)
This study aims to determine students’ perception of using Grammarly applications in their writings and the advantages and disadvantages of the Grammarly application for writing the English Language Education Study Program students. The researcher used mixed methods in this study with research instruments, namely interviews and questionnaires. The sample of this study was 13 students of the Manado State Islamic Institute of English Education Study Program of the 2018/2019 Academic Year who knew and used the Grammarly application. Data analysis in this study uses two analytical techniques. First, the qualitative analysis uses the Miles and Huberman model to analyze the results of interview data, and the second quantitative analysis uses descriptive statistics to analyze the results of questionnaire data. Based on the research results, 72.32% of students have positive perceptions of using this grammar application. It is reinforced by the results of interviews where respondents feel many benefits after using grammar applications, such as making it easier to correct grammar, spelling, punctuation, and styles, time -stream, and correction suggestions from applications that are easy to understand. On the other hand, 27.68% of students look negatively at using this application. It requires smooth network access and extensive storage capacity to use applications.